Are patients asked to consent to having a blood sample taken? - Wroński, Konrad; Cywiński, Jarosław; Bocian, Roman; Depta, Adam; Dziki, Adam (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2009)
Introduction: Both in out-patient rooms and in hospitals, taking blood samples from patients is one of those medical procedures to which the patient must give his/her consent. In the case of a medical procedure in which someone’s bodily integrity is to be disturbed, the doctor must inform the patient precisely about the scope of the procedure. Objectives: The objective of this research was to establish whether patients were asked to give their consent before having a blood sample taken. Material and methods: A group of 500 patients staying in Pirogow Hospital in Lodz was requested to fill in a survey prepared by the authors, in which tools were used to examine if patients were asked to give their consent before having a blood sample taken. The necessary calculations were done using STATISTICA 7.1 and EXCEL 2008. Results: The analysis of the results showed that 394 (78.8%) respondents had not been asked to give their consent before a blood sample was taken for laboratory examination and 106 (21.2%) respondents declared that they had. In 469 (93.8%) patients the doctor informed them thoroughly about the kind of examination the blood would be used for, whereas 31 (6.2%) respondents had not received this information. Conclusions: The vast majority of patients were not asked to give consent to having a blood sample taken for laboratory examination. The medical staff should know precisely the regulations referring to this procedure.